2018
DOI: 10.1590/1678-4766e2018003
|View full text |Cite
|
Sign up to set email alerts
|

Riqueza de galhas de insetos em áreas de Caatinga com diferentes graus de antropização do estado da Bahia, Brasil

Abstract: RESUMO O conhecimento sobre galhas de insetos da Caatinga ainda é fragmentado, com grande parte do esforço científico concentrado em alguns poucos pontos nos estados de Pernambuco e Bahia. Este estudo teve como objetivo verificar a ocorrência de galhas entomógenas e realizar sua caracterização morfológica em áreas de Caatinga de Ibiassucê, Estado da Bahia, com diferentes intensidades de ação antrópica. Foram selecionadas três áreas com base nos seus diferentes graus de antropização. Em cada área amostrada fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
5
11
1
1
Order By: Relevance
“…The prevalence in our study of gall induction on leaves confirms the worldwide pattern observed since Felt (1940) and Mani (1964), and reinforced in previous inventories carried out in the Caatinga (Santos et al, 2011;Costa et al, 2014;Brito et al, 2018). As a general pattern, the globoid and fusiform morphotypes stood out as the most frequent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence in our study of gall induction on leaves confirms the worldwide pattern observed since Felt (1940) and Mani (1964), and reinforced in previous inventories carried out in the Caatinga (Santos et al, 2011;Costa et al, 2014;Brito et al, 2018). As a general pattern, the globoid and fusiform morphotypes stood out as the most frequent.…”
Section: Discussionsupporting
confidence: 91%
“…Galls in the Caatinga biome began to be investigated only recently, with the first survey dating from 2011 (Santos et al 2011). Currently there are data for the states of Ceará, Pernambuco, Alagoas, and Bahia (Carvalho-Fernandes et al 2012, Costa et al 2014b, Nogueira et al 2016, Alcantara et al 2017, Brito et al 2018. However, the aspect that stands out about the occurrence of galls in this biome is the limited knowledge and the low number of inventories as compared to other Brazilian biomes such as the Atlantic Forest and Cerrado (Mendonça et al 2008, Stehmann et al 2009, Araújo et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Um realizado por Carvalho-Fernandes et al (2012) e o outro por Brito et al (2018) ambas pesquisas estudaram os efeitos das atividades antrópicas em comunidades de insetos galhadores em áreas de Caatinga, contudo os resultados foram divergentes. Carvalho-Fernandes et al (2012) constataram uma riqueza maior de morfotipos de galhas nas áreas preservadas do que nas áreas intermediárias e antropizadas, enquanto Brito et al (2018) encontraram uma riqueza de galhas maior nas áreas intermediárias quando comparadas às áreas preservadas e antropizadas. Porém, ambos estudos, ressaltaram que os insetos galhadores podem ser úteis na avaliação do impacto humano sobre o ambiente.…”
Section: Resultsunclassified
“…The results corroborate the hypothesis that families with the highest number of plant species have proportionally the highest number of gall-forming species (Fernandes 1992;Mendonça 2007). Leguminosae is one of the main host families of galls in different Brazilian habitats (Araújo et al 2019, Santos-Silva and Araújo in press) such as caatinga (e.g., Carvalho-Fernandes et al 2012;Brito et al 2018), cerrado (Coelho et al 2009;Silva et al 2018;Vieira et al 2018), caatinga-cerrado transition areas (Costa et al 2014a, b;Nogueira et al 2016), and restinga (Maia et al 2008;Maia and Oliveira 2010). Myrtaceae also plays an important role in gall inventories conducted in Brazil (Maia 2013a(Maia ,b, 2014Maia and Souza 2013).…”
Section: Discussionmentioning
confidence: 99%